Perceptions of HIV‐related health services in Zambia for people with disabilities who are HIV‐positive. Issue 2 (23rd April 2014) - Nixon, Stephanie A; Cameron, Cathy; Hanass‐Hancock, Jill; Simwaba, Phillimon; Solomon, Patricia E; Bond, Virginia A; Menon, Anitha; Richardson, Emma; Stevens, Marianne; Zack, Elisse
Abstract : Introduction: Despite the emerging body of literature on increased vulnerability to HIV among people with disabilities (PWDs), there is a dearth of evidence related to experiences of PWDs who have become HIV‐positive. This priority was identified by a disability advocacy organization in Lusaka, Zambia, where the prevalence of HIV and of disability is each approximately 15%. The purpose of this study was to explore perceptions and experiences of HIV‐related health services for PWDs who are also living with HIV in Lusaka, Zambia. Methods: This qualitative, interpretive study involved in‐depth, semi‐structured, one‐on‐one interviews with two groups of participants in Lusaka, Zambia: 21 PWDs who had become HIV‐positive, and 11 people working in HIV and/or disability. PWDs had physical, hearing, visual and/or intellectual impairments. Interviews were conducted in English, Nyanja, Bemba or Zambian sign language. Descriptive and thematic analyses were conducted by a multidisciplinary, international research team. Results: Participants described their experiences with HIV‐related health services in terms of the challenges they faced. In particular, they encountered three main challenges while seeking care and treatment: (1) disability‐related discrimination heightened when seeking HIV services, (2) communication barriers and related concerns with confidentiality, and (3) movement and mobility challenges related to seeking care and collecting antiretroviral therapy. These experiences were further shaped by participants' profound concerns about poverty and unmet basic needs. Discussion: This study demonstrates how PWDs who are HIV‐positive have the same HIV care, treatment and support needs as able‐bodied counterparts, but face avoidable barriers to care. Many challenges mirror concerns identified with HIV prevention, suggesting that efforts to promote inclusion and reduce stigma could have widespread benefits. Conclusions: Despite the growing body of literature on increased risk of exposure to HIV among HIV‐negative PWDs, this is the first published study to examine perceptions of testing, treatment and other HIV services for PWDs who have become HIV‐positive. Findings reveal far‐reaching opportunities for improving the quality of care for this population.